The emergency medical service dispatch recommendation system using simulation based on bed availability - Yeong-Yuh Xu; Shao-Jen Weng; Ping-Wen Huang; Lee-Min Wang; Chih-Hao Chen; Yao-Te Tsai; Ming-Che Tsai (BMC Health Services Research)
Abstract Objective The number of patients using emergency medical services (EMS) through ambulance dispatch has been increasing annually in Taiwan. Due to limited medical resource allocation, patients may not get on-time admission after they are sent to a hospital Emergency Department. This study aimed to construct a forecasting system to predict the availability of ED and ICU beds. Materials and methods A simulation-based forecasting system integrated with Google Maps is proposed to provide ED recommendations for ambulance dispatch. The web crawler technique continuously collects open data from the emergency information systems. An arrival transfer mechanism was proposed to convert the raw data into a simulation input. The results were then integrated with hospital assessment and routing distance in Google Maps to provide the most appropriate hospital ED to which a patient should be sent. Results The results provided forecast accuracy for bed availability for the next 20, 40, and 60 min in 10 selected hospitals in central Taiwan. In most hospitals, the forecasting accuracy is high. For example, the ED and ICU bed availability accuracies in the next 20, 40, and 60 min are [100%, 88.7%], [100%, 90.5%], and [100%, 92.1%]. The two scenarios also showed hospital recommendations based on the available beds, routing distance, and eight-dimensional assessments. Conclusion Previous EMS research usually did not consider future bed availability as the research target. This study predicted future bed availability and recommended the most appropriate hospitals for EMS dispatchers.